Connecting two arrays: the emerging role of actin-microtubule cross-linking motor proteins - Schneider, René; Persson, Staffan (Frontiers in Plant Science, 2015)
The cytoskeleton of plant cells, consisting of actin filaments (AFs) and microtubules (MTs), is a central structure for various intracellular processes, such as cell division, isotropic and polar growth, vesicle transport, cell shape and morphogenesis. Pharmaceutical and genetic studies have provided indications for interdependent cross-talk between the cytoskeletal components. Recent live-cell imaging studies have cemented this notion, in particular when the cytoskeleton rearranges. However, the proteins that directly mediate this cross-talk have remained largely elusive. Recent data indicate that certain proteins can interact with both cytoskeletal arrays at the same time, and hence connecting them. In this review, we summarize the recent literature of the AF- and MT-interactors, mainly focusing on a plant-specific mediator of cytoskeletal cross-talk: the calponin homology (CH) domain-containing kinesin-14 motor proteins (KCHs).